Welfare and Redistribution Effects of Alternative Tariffs in Energy Markets with Solar Power - Doina Radulescu; Nicola Pavanini; Fabian Feger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Renewable energy production via photovoltaic (PV) installations has increasingly taken off during the last years. This trend is desirable from an environmental perspective, but it challenges the financing of utilities' energy infrastructure networks. This happens because buildings with PV installations still require energy from the network, leaving the fixed costs of grid maintenance unchanged, but contribute less to the grid costs, as they mostly pay volumetric charges and intermittently produce their own energy. In this paper we propose an alternative tariff scheme to both incentivize PV adoptions and guarantee the sustainability of network costs. We use detailed data on energy consumption, income, wealth, and building characteristics for around 180,000 households in the Canton of Bern (Switzerland) in the years 2008-2013 to estimate models of energy demand and PV installation. We identify energy demand elasticities using a matching boundary discontinuity design that exploits price variation at spatial discontinuities, and we model PV adoption as a dynamic single agent investment framework. Using a counterfactual exercise we find that under a uniform tariff scheme low income households would experience a very small welfare loss.
Keywords: Q42; L94; D31; 330